Allogeneic hematopoietic cell transplantation improves outcome of adults with t(6;9) acute myeloid leukemia: results from an international collaborative study - Kayser, Sabine; Hills, Robert K; Luskin, Marlise R; Brunner, Andrew M; Terré, Christine; Westermann, Jörg; Menghrajani, Kamal; Shaw, Carole; Baer, Maria R; Elliott, Michelle A; Perl, Alexander E; Ráčil, Zdeněk; et al. (Haematologica, 2020)
Acute myeloid leukemia (AML) with t(6;9)(p22;q34) is a distinct entity accounting for 1-2% of AML cases. A substantial proportion of these patients have a concomitant FLT3-ITD. While outcomes are dismal with intensive chemotherapy, limited evidence suggests allogeneic hematopoietic cell transplantation (allo-HCT) may improve survival if performed early during first complete remission. We report on a cohort of 178 patients with t(6;9)(p22;q34) within an international, multicenter collaboration. Median age was 46 years (range: 16-76), AML was de novo in 88%, FLT3-ITD was present in 62%, and additional cytogenetic abnormalities in 21%. Complete remission was achieved in 81% (n=144), including 14 patients who received high-dose cytarabine after initial induction failure. With a median follow up of 5.43 years, estimated overall survival at five years was 38% (95%CI: 31-47%). Allo-HCT was performed in 117 (66%) patients, including 89 in first complete remission. Allo-HCT in first complete remission was associated with higher 5-year relapse-free and overall survival as compared to consolidation chemotherapy: 45% (95%CI: 35-59%) and 53% (95%CI: 42-66%) versus 7% (95%CI: 3-19%) and 23% (95%CI: 13-38%), respectively. For patients undergoing allo-HCT, there was no difference in overall survival rates at five years according to whether it was performed in first [53% (95%CI: 42-66%)], or second [58% (95%CI: 31-100%); n=10] complete remission or with active disease/relapse [54% (95%CI: 34-84%); n=18] (P=0.67). Neither FLT3-ITD nor additional chromosomal abnormalities impacted survival. In conclusion, outcomes of t(6;9)(p22;q34) AML are poor with chemotherapy, and can be substantially improved with allo-HCT.
Keywords: akutní myeloidní leukemie; Adult; lidé středního věku; Remission Induction; transplantace hematopoetických kmenových buněk; dospělí; retrospektivní studie; cytarabin; lidé; Middle Aged; Humans; Disease-Free Survival; Retrospective Studies; Leukemia, Myeloid, Acute; Cytarabine; přežití bez známek nemoci; indukce remise; Hematopoietic Stem Cell Transplantation